Return-to-play criteria based on infrared thermography during anterior cruciate ligament rehabilitation in football players - Escamilla-Galindo, Victor-Luis; Felipe, José Luis; Alonso-Callejo, Antonio; Van-der-Horst, Ralph; Torre-Combarros, Ana de la; Minafra, Paolo; Fernández-Muñoz, Daniel; Fernández-Cuevas, Ismael (Biology of Sport, 2025)
Reconstruction of the anterior cruciate ligament (ACL) is associated with degenerative changes during the return-to-play (RTP) process. Infrared thermography, due to its usefulness in monitoring the state of tissues, could help establish physiological criteria for monitoring the knee joint. The aim of the study was to describe normative skin temperature (Tsk) asymmetry of the knee region of interest (knee ROI) from football players during the ACL RTP process. Thirty professional and semi-professional football players, both male and female, from three different European leagues (age: 26.84±3.46 years; height: 1.83±0.22 m; weight: 75.38±5.92 kg) were evaluated using thermography during their RTP process. A linear mixed model was then developed in which Tsk asymmetry was the dependent variable. Sex and Day were included as predictor variables with fixed effects. Athlete was included as a random effect with (Model 1 and Model 2) and without (Model 3) interaction with Day. Model 2 was fitted with a random intercept and random independent slopes, and Model 3 was fitted with a random intercept and random dependent slopes. The results showed the estimates of the model in which both predictor variables were significant. The asymmetry decreased during the days after surgery (-0.01 per day after surgery). The results might help to establish an objective criterion based on infrared thermography for monitoring the rehabilitation stages in the RTP of football players during one year of evolution. The assessment of the thermal asymmetries of the knee ROI during the RTP established a Tsk progression criterion. Medical and technical staff could implement an infrared thermography tool for knee monitoring between RTP stages.